Application of modified nursing shift schedule based on SBAR communication model in perioperative management of patients with early gastric cancer (基于SBAR模式改良护理交班表在早期胃癌患者围手术期管理中的应用) - DANG Limei (党李梅); GUAN Chengguo (管成果); ZAI Xiaojuan (宰小娟) (中西医结合护理)
Objective To evaluate the effect of modified nursing shift schedule based on SBAR communication model in perioperative management of patients with early gastric cancer. Methods Totally 100 patients who received endoscopic submucosal dissection (ESD) for early gastric cancer between January and May 2021 were included as the control group, another 100 patients who received ESD for early gastric cancer between August and December 2021 were included as the observation group. The routine nursing shift management was adopted in the control group, and the modified nursing shift schedule based on SBAR communication model was carried out in the observation group. The quality of nursing shift, patient’s satisfaction and nurse’s critical thinking ability were measured and compared between two groups. Results After implementation of modified nursing shift schedule, the quality of nursing shift was improved, and nurses achieved a higher score of The California Critical Thinking Disposition Inventory (CCTDI) compared with that before implementation of modified nursing shift schedule (259. 95±38. 60 vs. 228. 68±36. 44, P＜0. 05). The score of satisfaction assessment in the observation group was higher than that in the control group (21. 47±2. 96 vs. 7. 39±2. 90, P＜0. 05). Conclusion The modified nursing shift schedule based on SBAR communication model is an effective tool of improve quality of nursing shift, patient’s satisfaction and nurse’s critical thinking ability. (目的 探讨基于SBAR模式改良护理交班表在早期胃癌患者围手术期管理中的应用效果。方法 选取2021年1月—5月医院消化内科收治的100例行内镜黏膜下剥离术(ESD)治疗的早期胃癌患者作为对照组, 2021年8月—12月收治的100例行ESD治疗的早期胃癌患者作为观察组。对照组使用传统交班模式, 观察组采用基于SBAR模式改良的护理交班表完成护理交班管理。评估两组的交班质量、患者对护士的满意度及护士的评判性思维能力。结果 实施改良护理交班表后, 护士交班质量全面性明显提高, 护士的评判性思维得分(259. 95±38. 60)分也高于实施前的(228. 68±36. 44)分, 差异有统计学意义(P＜0. 05)。观察组患者对护士满意度评分(21. 47±2. 96)分, 高于对照组的(17. 39±2. 90)分, 差异有统计学意义(P＜0. 05)。结论 采用基于SBAR模式改良的护理交班表可以提高交班质量以及患者对护士的满意度, 还能提高护士的评判性思维能力。)